Climate projections over the Antarctic Peninsula region to the end of the 21st century. Part III: clouds and extreme precipitation - A. Chyhareva; S. Krakovska (Ukrainian Antarctic Journal, 2022)
This paper focuses on the parameters that represent the characteristics of clouds and extreme precipitation events over the Antarctic Peninsula region, where clouds and precipitation play a crucial role in regional climate warming, particularly when a higher fraction of precipitation becomes liquid. In this work, we assess cloud and precipitation properties under climate change over the Antarctic Peninsula region under the Representative Concentrations Pathways (RCP) scenarios using model outputs of the Coordinated Regional Downscaling Experiment for polar regions (Polar CORDEX) for the 21st century. A similar approach was previously applied by authors for estimating projected changes in the temperature regime (Part I) and wet/dry indices (Part II) for the Antarctic Peninsula. We evaluated changes in cloud ice and condensed water contents, spatial distributions of both rain fraction and 95th percentile of total precipitation for the future periods, 2041–2060 and 2081–2100, for RCP4.5, RCP8.5 comparing them to the historical period of 1986–2005. We found that changes in studied parameters have similar tendencies and patterns under both scenarios, with more remarkable changes for the RCP8.5 scenario through the end of the 21st century. Analysis of obtained projections shows that all cloud amounts, liquid content in clouds, the annual fraction of rain in precipitation events, and frequency of extreme precipitation events will increase over the Antarctic Peninsula by the end of the 21st century under both RCP scenarios. The most significant changes are expected for the west coast and over the ocean to the west of the Antarctic Peninsula region, while the lowest changes are projected for the ridge of the Antarctic Peninsula mountains. However, the rates of expected changes vary within the broad Antarctic Peninsula region. While extreme event intensities will increase over the whole area, the changes will be most remarkable over the northwestern slopes of the Antarctic Peninsula, where Akademik Vernadsky station is located.